Technical feasibility and safety of an intraoperative head‐up display device during spine instrumentation. Issue 3 (29th August 2016) - Yoon, Jang W.; Chen, Robert E.; Han, Phillip K.; Si, Phong; Freeman, William D.; Pirris, Stephen M.
Abstract: Background: The primary aim of this study was to determine the safety and feasibility of capturing and streaming neuronavigation images onto a head‐up display during spine instrumentation. Methods: Using a novel device, neuronavigation images were captured and transferred wirelessly via a password‐encrypted network to the head‐up display. At the end of the procedure, the surgeons completed a survey to gather their opinions of the system. Results: Forty pedicle screws were placed using the head‐up display. The average screw placement time was slightly shorter when the head‐up display was used (4.13 min with vs. 4.86 min without). The post‐procedure survey demonstrated that 79% of surgeon's responses were positive. Conclusion: A wearable head‐up display can benefit current neuronavigation systems, but larger, outcomes‐based trials are needed. Higher processing speed would allow streaming of higher resolution images. Along with an enlarged display, these may significantly improve utilization of this technology. Copyright © 2016 John Wiley & Sons, Ltd.